2020
DOI: 10.1186/s12883-020-01825-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronically reduced IL-10 plasma levels are associated with hippocampal sclerosis in temporal lobe epilepsy patients

Abstract: Background: Increasing evidence supports the role of soluble inflammatory mediators in the pathogenesis of refractory temporal lobe epilepsy (TLE). Hippocampal sclerosis (HS) is a well-described pathohistological abnormality in TLE. The association of proinflammatory cytokines with epileptic disease profiles is well established; however, the potential significance of circulating interleukin 10 (IL-10), particularly in TLE-associated HS, is still poorly understood. Therefore, taking into consideration the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…Only one of nine responder patients had TLE, and the remaining had extra TLE or multifocal epilepsy, moreover, only two of 13 nonresponder patients had TLE. Considering the proinflammatory immune status as a principal component in TLE 10 , 14 , lower pre-DBS IL-10 levels in responders are unlikely to be a result of the epilepsy type, but the finding rather suggests the presence of an inadequate systemic anti-inflammatory immune response as one of the pathophysiological characteristics of chronic epilepsy 18 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Only one of nine responder patients had TLE, and the remaining had extra TLE or multifocal epilepsy, moreover, only two of 13 nonresponder patients had TLE. Considering the proinflammatory immune status as a principal component in TLE 10 , 14 , lower pre-DBS IL-10 levels in responders are unlikely to be a result of the epilepsy type, but the finding rather suggests the presence of an inadequate systemic anti-inflammatory immune response as one of the pathophysiological characteristics of chronic epilepsy 18 .…”
Section: Discussionmentioning
confidence: 94%
“…Taking into account the broad anti-inflammatory role of IL-10, an animal study revealed the role of IL-10 in the inhibition of IL-1beta production and inflammasome activation in microglia in response to epileptic seizures, suggesting a role for IL-10 in epilepsy treatment 17 . Recently, we detected reduced plasma IL-10 levels in patients with DRE, suggesting the presence of an inadequate systemic anti-inflammatory immune response during chronic epilepsy 18 .…”
Section: Introductionmentioning
confidence: 93%
“…Leo et al [21] demonstrated that anti-IL-6R antibodies were effective in reducing the number of absence seizures and depression-like behavior in a rat model of convulsive epilepsy, and they concluded that IL-6 plays an important role in seizure induction and seizure process. Basnyat et al [22] demonstrated that serum levels of IL-10 were significantly lower in patients with refractory TLE and that IL-10 levels showed a negative relationship with the course of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…With a strong anti-inflammation effect, IL-10 is known to suppress seizures in epilepsy patients by reducing the expression of interleukin-1 [34]. There is a significant negative correlation between plasma IL-10 levels and the prolongation of seizure time, while the continuous decrease of IL-10 has a significant positive correlation with hippocampal sclerosis in patients with epilepsy [35]. The significance of IL-10 in epilepsy remains controversial because some studies have reported that the level of IL-10 in patients with epilepsy is increased instead of decreased.…”
Section: Interleukinmentioning
confidence: 99%